Influence of Bio-organic Fertilizers on Tomato Plants Growth under Deep Tillage Preparation in Western Omdurman Soil - Marajan, Wael A; Hadad, Mohammed A; Gafer3Mohammed O; Khalifa, Khalifa M; Hatim, Sulfab A; Abdelrhman, Musa A (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study was conducted in season (2014/2015) at small Farm in Western Omdurman, Khartoum State, Sudan. The main objective of this study was to study the effect of bio-organic fertilizers on growth component of tomato plants. The experiment was arranged in randomised complete block design (RCBD) with four replication and 7 treatments. The experimental treatments were as follows: Compost application 15t ha-1, inoculation of Azotobacter spp. and Mycorrhizal fungi and their combinations with compost. Statistical analysis (spss) was used to test the effects of treatments on different parameters. The results revealed that compost application alone in this season had affect on the shoot fresh and dry weight of tomato plants rather than root fresh and dry weight. Inoculation of Azotobater spp in combination with compost showed increase on tomatoes growth components compared to the control and Azotobacter spp alone. Mycorrhiza treatment to tomato plants alone showed an increase in plant growth components compared to the control and that in combination with compost. Application of biofertilizers both Azotobacter and Mycorrhiza in combination with compost 15 t ha-1 showed a positive effect on tomato growth components including plant height, shoot fresh and dry weight, and root fresh and dry weight